Projeto e implementação de um conversor módulo integrado para conexão de geração fotovoltaica à rede elétrica - Andres, Bernardo (2018)
This Master Thesis presents the analysis, design and implementation of a grid-connected module integrated converter, or, simply, microinverter, for photovoltaic applications. The system is composed of two stages: a isolated DC-DC converter and a DC-AC converter (inverter). This proposed micro inverter has a DC bus (DC link), decoupling both stages, allowing to make the project, design and implementation of both individually. The first stage is a zero voltage switching DC-DC full bridge, with phase-shift modulation, and the second stage is a DC-AC full bridge with unipolar pulse-width modulation. Briefly, the first stage provides high voltage gain, besides isolation between the photovoltaic module and the electrical grid, in order that inverter bus has enough voltage to perform grid connection. This connection is made by inverter with output inductive filter. In order to extract the maximum power of photovoltaic module, the maximum power point tracking (MPPT) is made indirectly, controlling inverter bus voltage. Thus, the DC-DC converter operates in open loop, so that system control is design and implementated only on second stage. So, in this way, this Master Thesis contributes developing a microinverter employing classical converter topologies, with high efficiency and simplicity of design and implementation, using just two control loops, in a way that external voltage loop should be able to perform MPPT, ensuring maximum power harvesting of photovoltaic module, and the internal current loop should be able to control active power flow to electrical grid by controlling the current. In order to accomplish MPPT properly, the ripple of 120 Hz in voltage and current of photovoltaic module, generated by pulsed single phase grid power, should have low amplitude. Besides that, in order to be in compliance with standards of grid connection, as total demand distortion and power factor, among others, the current controller project should take into account the inffluence of main harmonic components of grid voltage. Experimental results are presented to prove the micro inverter performance.